ANALISIS KONDISI KOMPONEN-KOMPONEN TEKNOLOGI PENGOLAHAN DI INDUSTRI TEH CURAH INDONESIA - Rohayati Suprihatini E.Gumbira Sa’id , Marimin dan Djumali Mangunwidjaja (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTIn order to accelerate increasing of technology capability of  made tea industries in Indonesia, it requires study on  technology components. Surveys was conducted on eight  made tea companies.  Ordered weighted averaging (OWA) analysis was applied to determine level of technology components condition.  Non numeric multi-criteria multi-person analysis was applied to determine the level of technology capability in Indonesian made tea industry. The research results  show that the level of technology component condition namely technoware, humanware, infoware, and orgaware  are still in medium level, respectively.  The technology component condition should be in high level, in order to increase  technology capability to medium level.  In term of strategic management of improving the capability of technology, most of respondents (75%) selected improvement continuously. Therefore, this strategy should be treated as an action program of Indonesian Tea Association (ITA) as well as government.Keywords : capability, technology, processing, made tea.